Capital social e desenvolvimento local na perspectiva de redes sociais dos produtores de café sombreado no Maciço de Baturité, Ceará - Braga, Francisco Laercio Pereira (2022)
The Maciço de Baturité region was contemplated by strategic plans focused on stimulating the local development of the demand for incentives for some agricultural activities, in the case of coffee, and non-agricultural ones, in the case of rural tourism. In this context, this thesis is structured in three essays referring to the Maciço de Baturité region in the state of Ceará. The first essay is called “Spatial analysis of economic development related to the Maciço de Baturité Region - CEARÁ (2010)”, in which our objective was to analyze the relative multidimensional economic dynamism of Ceará’s municipalities and their spatial distribution in 2010, with particular emphasis on those that make up the Maciço of Baturité region. For this, the project was based on the use of the factor analysis and cluster analysis techniques. In the second moment, an exploratory spatial analysis was carried out using the Global and Local Moran Index. The results revealed the existence of positive spatial autocorrelation for the state of Ceará and negative for the Maciço region. The second essay is called “Analysis of Social Networks: the case of shaded coffee rural producers in the region of Maciço de Baturité – Ceará”, in which we analyze the profile of access to information in the shade-grown/ecological coffee production network in the Maciço de Baturité region, in the state of Ceará. Through the Analysis of Social Networks (ARS), the main agents (actors) that are directly related to the cultivation of shadegrown coffee were identified. It was concluded that information circulates at a lower speed on the network and that there is still little interaction between the actors that form it. Finally, the third essay is called “Social capital and its effects on the network of shade-grown coffee producers in the Maciço de Baturité region – Ceará”, based on the assessment of the level of social capital present in the network of shade-grown coffee producers in the Maciço de Baturité region. The results made it possible to characterize the shade-grown coffee production network (production, governance, learning and innovation) and to assess the social capital, in which the network of producers fits with a medium level of social capital (Social Capital Index - ICS), identifying the cognitive social capital dimension as the one that most contributed to the measurement of ICS.